2019
DOI: 10.1186/s40814-019-0520-8
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of mifepristone medical abortion in Canada: pilot and feasibility testing of a survey to assess facilitators and barriers

Abstract: Background: Direct primary care provision of first-trimester medical abortion could potentially address inequitable abortion access in Canada. However, when Health Canada approved the combination medication Mifegymiso® (mifepristone 200 mg/misoprostol 800 mcg) for medical abortion in July 2015, we hypothesized that the restrictions to distribution, prescribing, and dispensing would impede the uptake of this evidence-based innovation in primary care. We developed and pilot-tested a survey related to policy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
(62 reference statements)
0
20
0
Order By: Relevance
“…The survey instruments used in this study were developed and tested following methods described elsewhere 51 52. Additionally, we conducted a rigorous process to develop and test the surveys used to measure implementation of mifepristone 40. The process for adapting and pilot testing the surveys for the present study is described in a forthcoming publication.…”
Section: Methodsmentioning
confidence: 99%
“…The survey instruments used in this study were developed and tested following methods described elsewhere 51 52. Additionally, we conducted a rigorous process to develop and test the surveys used to measure implementation of mifepristone 40. The process for adapting and pilot testing the surveys for the present study is described in a forthcoming publication.…”
Section: Methodsmentioning
confidence: 99%
“…As medical abortion counselling may require additional time and resources inadequately reflected in a pharmacist's dispensing fee, our data indicate this may act as an additional barrier to provision for some pharmacists. Ongoing research 3,[32][33][34][35] suggests that 3 years since mifepristone/misoprostol for medical abortion entered the Canadian market in January 2017, uptake continues to be variable across Canada. Several pharmacy managers in our study reported using the Pharmacist Checklist and Resource Guide to train staff pharmacists for medical abortion provision. Indeed, a strength of our study was our integrated knowledge translation strategy for engaging knowledge users throughout the research process.…”
Section: Discussionmentioning
confidence: 99%
“…As medical abortion counselling may require additional time and resources inadequately reflected in a pharmacist’s dispensing fee, our data indicate this may act as an additional barrier to provision for some pharmacists. Ongoing research 3 , 32 - 35 suggests that 3 years since mifepristone/misoprostol for medical abortion entered the Canadian market in January 2017, uptake continues to be variable across Canada.…”
Section: Discussionmentioning
confidence: 99%
“…The development of the 14-question interview guide [17] was based on Rogers' theory [13] and its application in Table 1. Changes of baseline restrictions of Health Canada (2015) [7,9,42] and the College of physicians of Quebec (2017) [11,25,[43][44][45].…”
Section: Methodsmentioning
confidence: 99%